Serendipitous Diagnosis of Adenocarcinoma of the Mandible Metastasized from the Prostate: A Case Report - Krishna Satpathy; Kunal Agarwal; Priyanka Debta; Fakir Mohan Debta (Journal of Indian Academy of Oral Medicine and Radiology)
Prostate cancer is among the most prevalent malignancies in males. Although bone metastases from prostate cancer are common, mandibular metastases are unlikely. Mandibular metastatic carcinoma accounts for less than 1% of all oral malignancies and can cause a diagnostic conundrum. Here, we present a rare case of a 56-year-old male with metastatic adenocarcinoma of the prostate involving the mandible and the evaluation criteria that can help determine the metastatic lesion.